مركز الضبط وعلاقته بتوكيد الذات - سحنون فاطمة; كعباش جهاد; جمال فطام (My University, 2022)
The current study aims to reveal the relationship between the center of control and self-assertion among a sample of students of the Faculty of Social Sciences at the University of Laghouat. The two students will rely on the descriptive approach to suit the nature and objectives of the study, and the questionnaire is adopted as a means of data collection. The problem of our study is determined by the following questions: - Is there a relationship between the control center and the self assertion of the sample members? - Are there differences between the sexes in the control center (internal and external) - Are there gender differences in the level of self-affirmation?
لدى عينة من طلبة كلية العلوم الاجتماعية بجامعة عمار ثليجي –الاغواط-